Relugolix Combination Improves Quality of Life in Phase 3 Studies of Symptomatic Uterine Fibroids [OP04-4D]. (May 2020) - Lukes, Andrea S.; Poindexter, Alfred; Villarroel, Claudio; Li, Yulan; Hunsche, Elke; Stewart, Elizabeth A.
Abstract : INTRODUCTION: In the two phase 3 LIBERTY Institutional Review Board-approved studies, relugolix combination therapy (Relugolix-CT; once-daily relugolix 40 mg, estradiol 1.0 mg, and norethindrone acetate 0.5 mg) significantly improved heavy menstrual bleeding (HMB) and pain associated with uterine fibroids (UF). Impact of Relugolix-CT treatment on quality of life (QoL) was assessed using the validated Uterine Fibroid Symptom (UFS)-QoL questionnaire. METHODS: Changes from baseline to Week 24 in UFS-QoL symptom severity (SS) and health-related (HR) QoL scale scores (range 0 to 100), and HR-QoL subscale scores were assessed. Higher SS scores reflect more severe symptoms; conversely, higher HR-QoL scores indicate better QoL. Least-squares mean changes in SS and HR-QoL were compared between Relugolix-CT and placebo, by LIBERTY study, using a mixed-effects model, with treatment, visit, region, baseline menstrual blood loss volume, and treatment by visit interaction as fixed effects. RESULTS: At Week 24, SS improved significantly from baseline (both studies: nominal P<.0001) with Relugolix-CT vs placebo (decreases were, respectively, from 55.1 to 23.4 and from 60.3 to 49.2 [LIBERTY-1]; from 59.1 to 21.7 and from 59.2 to 45.1 [LIBERTY-2]). HR-QoL improved significantly from baseline (both studies: nominal P<.0001) with Relugolix-CT vs placebo (increases were from 37.2 to 74.0 and from 33.5 to 44.9 [LIBERTY-1]; from 38.9 to 78.7 and from 37.3 to 51.0 [LIBERTY-2]). Similar results were observed between groups in all HR-QoL subscales. CONCLUSION: Over 24 weeks, Relugolix-CT significantly improved HMB and pain associated with UF, with corresponding significant improvements in patient-reported SS, and HR-QoL total and subscale scores.